Hempcrete – The Evolutionary Building Material - Wandhare, Aniket Narendra; Burange, Chinmay (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Due to increase in carbon emissions and its side effects, it is critical to reduce carbon footprints or focus on carbon-negative technologies. Plant-based construction materials with little environmental effect are quite advantageous in terms of preventing pollution. Bio-aggregate concrete provides not only multi benefits of low density, greater thermal insulation and low embodied energy, it can also make use of industrial wastes such as fly ash, slag, etc. One such material is hemp concrete. It is a composite made of hemp shives, hemp fiber and fly ash, slag, lime as binder. Hemp is one of the world’s oldest cultivated crops and has a wide range of applications, including construction. This paper discusses the mechanical properties and applications of hemp and hempcrete such as mechanical properties and durability, with a focus on its carbon negative ability and it focuses on its possible contribution towards solution of climate change problems.